PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KOMITMEN ORGANISASI PADA PT. PLN (PERSERO) UP3 MEDAN - Bela Safira; Hafiza Adlina (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
The goal of this study is to look at how leadership style and work environment affect organizational commitment at PT. PLN UP3 Medan. A quantitative research method with an associative approach is used in this work. Participants in this study were all employees of PT. PLN UP3 Medan. The sample size is 56 individuals, and the sampling method is saturation sampling. The primary data for this study was acquired by questionnaire distribution, while the secondary data was gathered via a literature review. Data analysis methods used include the validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The findings revealed that the leadership style (X1) had a significant impact on the organizational commitment variable (Y). While the workplace environment (X2) has insignificant impact on organizational commitment (Y). However, organizational commitment is influenced by both leadership style and work environment. According to the coefficient of determination test, the modified R square value of 0.190 suggests that 19.0% of the leadership style and work environment components may explain the organizational commitment variable. Meanwhile, remaining 81.0% is accounted by variables beyond this analysis.